GEOLOGI DAN PEMODELAN RESERVOIR STATIS 3D PADA FORMASI LOWER ARANG, LAPANGAN SEM, CEKUNGAN NATUNA BARAT - INDAHVINALDI, ANNISA
SEM Field is an abandoned offshore oil field yet the reserve had not been all produced. The field is located administrively in Natuna Island, province of Riau Island, Indonesia. This Field is covering an area of approximately 7,4 km2. Geologically, SEM Field is located in Tertiarry aged-West Natuna Basin. The study takes focus on Lower Arang Formation with four reservoirs interval consisting sandstones as its lithology respectively. The aim of this study are determinating geological model and estimating remaining reserve from four reservoirs. Data used in this study are wireline log, seismic (3D), and description of cutting and core. Several methods used in this study are, well data analysis that includes well correlation using sequence stratigraphy and petrophysic analysis; seismic data analysis that includes determinating the depth structure map and isopach map; static reservoir modeling that includes determinating the despositional environment of the facies, petrophysical modeling, oil-water contact and the estimation of original oil in place (OOIP) and reserve. The outcome from all of those methods are the geological setting of SEM Field and the estimation of its oil reserve. The main structural geology in SEM Field are an anticline with northeast-southwest orientation associated with reverse fault and normal faults with northeast-southwest orientation. Lower Arang Formation was deposited with transgressive cycle that developed the depositional environment from estuarin into shoreface to offshore transition. The estimation of original oil in place (OOIP) from four reservoirs is 31 MMSTB and still has remaining reserve around 11.52 MMSTB. Based on the result of modeling, SEM Field has 2 absorbtion points which are potentially will gain the production.